PENGARUH PROFITABILITAS DAN STRUKTUR MODAL TERHADAP HARGA SAHAM PADA PT JAPFA COMFEED INDONESIA TBK - Mustika, Esti; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on stock prices at PT Japfa Comfeed Indonesia Tbk. This type of research uses an associative method with a quantitative approach, using secondary data in the form of financial statements and stock prices during the observation period 2015-2024. The data were obtained through documentation techniques. The data analysis method used is multiple linear regression analysis with the help of SPSS software, including Classical Assumption Test, Partial Test (t-test), and Simultaneous Test (F-test).The results show that ROA has no significant partial effect on stock prices, and DER also has no significant partial effect on stock prices. Simultaneously, ROA and DER do not have a significant effect on stock prices. The coefficient of determination (R²) indicates that the independent variables have limited ability in explaining stock price variations, while the rest is influenced by other variables outside the model.